Development of an indicator framework for assessing nursing quality in interventional therapy for intracranial aneurysms in China - Yang, Hai-xia; Fan, Ben-fang; Zhao, Jia; Ji, Jian-hong; Ding, Wen-bin; Shen, Wei-guang (Frontiers in Neurology, 2024)
ObjectiveThe objective of this study is to devise an indicator system to assess the quality of nursing care in the context of interventional therapy for intracranial aneurysms (IA) in China. This will furnish a standardized and quantitative framework for the monitoring and assessment of nursing quality within the IA interventional therapeutic field.MethodsThe indicators and their associated weights within the evaluation system for nursing quality in interventional therapy for IA were determined based on the theoretical framework of the three-dimensional quality model, specifically the “structure-process-outcome” paradigm. This was achieved by using several methodological approaches, such as literature analysis, semi-structured interviews, expert consultations, the Delphi method, and the analytic hierarchy process.ResultsExpert consultations were conducted over two rounds, with questionnaires distributed via email and WeChat. Both rounds yielded a questionnaire return rate of 100%. Across these consultations, pertinent statistical measures were obtained, such as the expert authority coefficient (Cr), the coefficient of variation (CV), and Kendall’s harmony coefficient, which exhibited values of 0.886 and 0.952, 0–0.193 and 0–0.185, and 0.138 and 0.149, respectively. These findings indicated statistically significant differences (p < 0.01). Notably, the indicators within the final iteration of the evaluation system for nursing quality in interventional therapy for IA are categorized into 3 tiers: primary indicators, encompassing 3 metrics; secondary indicators, comprising 10 metrics; and tertiary indicators, consisting of 36 indicators.ConclusionThe indicator system devised for assessing nursing quality in interventional therapy for IA, as outlined in this study, possesses a high level of scientific rigor and reliability in China. It aptly captures the unique nuances inherent in IA management during interventional therapy nursing, thereby serving as a valuable reference point for the assessment of nursing quality within the context of IA interventional therapy.